Clinical and Therapeutic Characteristics of Pituitary TSH-Secreting Adenoma in Adolescent-Onset Patients: Six Case Studies and Literature Review - Yang, Yamei; Liu, Jie; Deng, Kan; Lu, Lin; Zhu, Huijuan; Lian, Xiaolan; Bao, Xinjie; Duan, Lian; Yao, Yong (Frontiers in Endocrinology, 2021)
Background: Thyrotropin-secreting adenoma (TSH-oma) is a very rare kind of functional pituitary adenoma, especially in adolescents. The potential clinical and therapeutic characteristics of adolescent-onset TSH-oma patients are still unknown. Objectives: The aim of the study was to summarize the clinical and therapeutic characteristics of adolescent-onset TSH-oma patients. Methods: We retrospectively analyzed 6 (4.1%) adolescent-onset TSH-oma cases from 148 patients who were diagnosed with TSH-oma at Peking Union Medical College Hospital between January 2012 and October 2020. A literature review was performed on the PubMed online database, and 14 adolescent-onset TSH-oma cases were retrieved. The characteristics of clinical manifestations, treatment outcomes and follow-ups were analyzed and compared with adult TSH-oma patients. Results: Altogether, 20 adolescent-onset cases were included in this study, and the mean onset age were 13.4±3.3 years old. Males were slightly predominant (M: F=1.5:1). The baseline TSH, FT3, and FT4 levels of adolescent-onset cases were 6.30(9.82) μIU/ml/ml, 9.18(11.61) pg/ml, and 3.22(1.90) ng/dl respectively, and all significantly higher than adult patients in our hospital, as well as the giant tumor ratio (36.8% vs 9.3%，p=0.007). Compared with all age patients in literatures, the biochemical remission rate of SSAs (57.1%), remission rate of TSS (38.9%) were considerably lower, and recurrence rate (44.4%) was considerably higher in adolescent-onset patients. Conclusions: Adolescent-onset TSH-oma patients have higher TSH and thyroid hormone levels, more giant tumors, and worse treatment outcomes than adult cases. early diagnosis, multidisciplinary therapy and close follow-up should be highlighted to improve prognosis.